Adhesive polyelectrolyte coating through UV-triggered polymerization on PLGA particles for enhanced drug delivery to inflammatory intestinal mucosa - Jie Zhang; Yi-jing Yin; Xing-wang Wang; Wei-qi Lu; Zhao-yang Chen; Chao-hui Yu; Ke-feng Ren; Cheng-fu Xu (Journal of Nanobiotechnology)
Abstract Administering medication precisely to the inflamed intestinal sites to treat ulcerative colitis (UC), with minimized side effects, is of urgent need. In UC, the inflammation damaged mucosa contains a large number of amino groups which are positively charged, providing new opportunities for drug delivery system design. Here, we report an oral drug delivery system utilizing the tacrolimus-loaded poly (lactic-co-glycolic acid) (TAC/PLGA) particles with an adhesion coating by in situ UV-triggered polymerization of polyacrylic acid and N-hydroxysuccinimide (PAA-NHS). The negatively charged carboxyl groups effectively interact with the positively charged focal mucosa, and the NHS ester groups form the covalent bonds with the amino groups, thereby synergically enhancing the adhesion of the PLGA particles to the focal mucosa. Our findings reveal that, compared to the naked particles, the PAA-NHS coating increases the adhesion of particles to the inflammatory intestine. In a dextran sulfate sodium-induced acute colitis mouse model, the TAC/PLGA particles with PAA-NHS coating exhibits substantial retention of TAC within the inflammatory intestine, enhancing drug delivery efficiency and therapeutic effects. This approach holds promise for UC management, minimizing systemic side effects and optimizing therapeutic outcomes. Graphical abstract